To examine the Influence of Gender Interaction on Academic Achievement of learners. - Irungu, Mwangi Newton; Nyagah, Grace; Mercy, Mugambi (Advances in Social Sciences Research Journal, 2019)
This article aimed at examining the influence of gender interaction on academic achievement of learners. the study targeted public secondary schools in Murang’a County, Kenya and focused on Chemistry subject matter. Descriptive survey design was adopted for this study, while the study was guided by two null hypotheses: Ho1: There is no statistically significant effect of gender interaction on academic achievement of learners in chemistry. Ho2: There is no statistically significant relationship between gender interactions and academic achievement of learners in Chemistry. The study was guided by social interaction principles advocated by Vygotsky Social development theory. A sample size of 32 public secondary schools, 384 form three students and 32 teachers of Chemistry were used for the study. Lesson Observational Checklist (LOC) was the main instrument for data collection while the Chemistry Achievement Test (CAT) provided scores for the dependent variable. Reliability and validation of the instruments were done through a pilot study in two public secondary schools that were not part of the sampled schools. The study was based on gas laws in Chemistry which is taught in form three class in term one while Quantitative and qualitative data was collected during that period. Results from the qualitative data revealed that, girls were more interactive than boys while the stereotype of classifying certain subjects as female or male ones is changing. Results from simple regression analysis indicated that, there is no statistically significant effect of gender interaction on academic achievement of learners in chemistry. The statistic coefficient (R2 = 0.013) provided the amount of variation that can be accounted for by the independent variable which is gender interaction, implying the model explained 1.3% variation in academic achievement which is the dependent variable in this study. Therefore 98.7% change in academic achievement resulted from other factors that were not part of the model. Analysis from Pearson Product-Moment Correlation Coefficient (r = 0.1137) yielded a weak positive relationship implying that, there is no statistically significant relationship between gender interactions and academic achievement of learners in chemistry. Therefore gender interaction does not contribute to learners’ academic achievement.